Non-genetic factors affecting growth performance of indigenous chicken in rural villages - N.H. Desha; M.S.A. Bhuiyan, F. Islam; A.K.F.H. Bhuiyan (Universiti Malaysia Kelantan, 2016)
The study was conducted to investigate the effect of non-genetic factors on growth performance of Indigenous chicken under village condition of Bangladesh. A total of 1070 eggs from Indigenous chicken were set and 628 chicks were hatched. Data were recorded on hatching performance and body weight of chicks from week 1 (BWWK1) to week 15 (BWWK15). The non-genetic factors considered were sex, batch, farm, brooding system and feeding system. Least squares means for fertility (%), hatchability (%) and mortality on hatching day (%) of eggs were 70.81, 77.52, and 19.63, respectively. Body weight of male and female birds at 1st, 3rd, 5th, 7th, 9th,11th, 13th and 15th weeks of age were 45.97 and 38.44 g, 129.36 and 104.94 g, 266.82 and 213.92 g, 453.93 and 390.72 g, 470.58 and 394.75 g, 614.60 and 489.48 g, 693.72 and 462.77 g, 833.94 and 650.77 g, respectively. Artificially hatched birds gained better body weight than the naturally hatched birds up to 11 weeks of age. The coal brooding system was superior to electric and natural brooding. Hand mixed feed gave better growth of birds than commercial feed and scavenging feed resources. Better growth of birds in farm 2 was observed suggesting replication of management system of farm 2 to get better growth. Further, batch, farm, brooding system and feeding system were found to contribute significant (p<0.05) differences in the body weight at various weeks of their age. These results indicated due adjustment of non-genetic management systems for obtaining better growth performance of Indigenous chicken to enhance commercialization of the indigenous chicken flocks in rural areas of the country.